Graph theoretic approach in analyzing the navigation paths of online learners - Bagarinao, Ricardo T. (2014)
The study looked at the navigational behavior of students in an online undergraduate course in Science, Technology, and Society (STS). It is grounded on the concept of movement ecology, which assumes that movement of organisms is mediated by both intrinsic and extrinsic factors. It applies the graph theoretic approach, where the course site pages were considered as the vertices while the links between two pages were considered as the edges. Gephi was used to visualize students' navigation patterns. Relative importance, number of visits, and navigation frequency for edges, vertices, and paths were computed.
The results showed that students tend to navigate the pages (i.e. resources pages and forum discussion page) that contain the information they need to achieve their learning goals and/or perform their academic tasks. These pages had a higher computed number of visits, RI values and navigation frequencies than the other pages. Most students have also navigated nonlinearly (i.e. acyclical) in the course site through some of them shown linear navigation patterns (i.e. acyclical). Nonlinear navigation patterns indicate that students had a full control over their navigation decisions while linear patterns indicate that students need some adaptive navigational advisement so. This difference should be considered in designing an online learning environment to make it responsive to individual learner's needs.
Keywords: Online learning